First record of Spiny Turtle Heosemys spinosa (Gray, 1831) (Testudines: Geoemydidae) on Babi and Lasia Islands, West Sumatran Islands, Indonesia - Silvi Dwi Anasari; Muhammad Iqbal; Tom Amey (BIO PALEMBANICA, 2025)
The Spiny Turtle Heosemys spinosa (Gray, 1831) is an endangered freshwater species found in parts of Southeast Asia, but records from offshore islands are scarce. This study documents the first occurrence of H. spinosa on Babi and Lasia Islands, off the west coast of North Sumatra, Indonesia. Between 15 October and 25 December 2023, nine individuals were observed on Lasia Island, and another on Babi Island in August 2025. The species was found in wet forest floors, mangroves, and leaf-littered habitats within protected forests. Both uninhabited islands retain extensive old-growth forest, suggesting they may serve as refuges for H. spinosa. This record expands the species’ known range and highlights the need for further research and conservation on Indonesia’s lesser-studied satellite islands.